Smoker desaturation during general anaesthesia: a case report - Mohamed, Abdul Hadi; Md Ralib, Azrina; Abdullah, Nor Zamzila; Osman, Ariff; Mat Nor, Mohd Basri (2009)
We report a sudden hypoxaemia during intubation and after extubation in patient was smoking few hour before surgery. The cause of his desaturation was not related to secretion in the upper airway but may be due to reduced oxygen tension in the body prior to surgery. We able to secure the airway and prevent prolonged of desaturation by intubating this patient during induction and after extubation. We excluded other cause of desaturation for example secretion, bronchospasm and also airway obstruction inn this case. We conclude that smoking cessation was necessary at long as possible even though in case of emergency to prevent potential hypoxaemia pre intubation and during extubation at the end of operation.